Interactions between rod and L-cone signals in deuteranopes: Gains and phases - Kilavik, B.E.; Kremers, Jan (Visual Neuroscience, 2006)
The dynamics of interactions between rod and L-cone driven signals were studied psychophysically in two deuteranopic observers. Flicker detection thresholds for different ratios of rod to L-cone modulation were measured at temporal frequencies between 1 and 15 Hz. A model, which assumes that rod and L-cone driven signals are vector added, can describe the threshold data adequately. We found that up to about 8-10 Hz temporal frequency, rod and L-cone signals interact additively, whereas at higher frequencies the interaction is subtractive. Rod and L-cone signal strengths depend similarly on temporal frequency and are maximal between 3 and 5 Hz. The phase difference between rod and L-cone signals increases linearly with temporal frequency, indicating that their responses have a delay difference of about 20 to 30 ms, consistent with involvement of the faster rod pathway. The data would suggest a nearly complete additivity of the rod and cone driven signals when using flashed stimuli. But, literature data showed only partial additivity of the two, suggesting that different postreceptoral mechanisms are involved in the two tasks.
Keywords: rod; L-cone; temporal frequency; gain; latency difference